PENINGKATAN KAPASITAS KADER POSYANDU MENGENAI GIZI SEIMBANG DAN STIMULASI TUMBUH KEMBANG PADA BALITA - Maghfirah, Luzvia; Asniar, Asniar; Maulina, Maulina (NURSE: Journal of Nursing and Health Science, 2024)
Background: Stunting is, as yet, one of the nutritional problems in Indonesia, which inhibits brain development and child growth. Health cadres, as health facilitators in the village, are expected to be able to assist the community in handling stunting cases. The lack of understanding among village health volunteers (VHV) regarding the prevention and treatment of stunting has led to insufficient treatment of stunting cases in Blang Bintang sub-district, Aceh Besar district. Method: This case study aims to describe the implementation of Community Health Nursing (CHN) care in the aggregate of under-fives with stunting through capacity building of VHV in posyandu (monthly health post) in one of the villages in Blang Bintang sub-district, Aceh Besar district. The community nursing assessment led to the CHN diagnosis of ineffective community coping. It was followed by designing community nursing care and its implementation through health education for VHV related to balanced nutrition and growth stimulation in toddlers with education and demonstration sessions. Pretest and posttest were conducted to evaluate knowledge and health cadres related to balanced nutrition and growth stimulation in toddlers. Results: The evaluation results showed an increase in two outcomes, namely health behavior knowledge and toddler care knowledge. Conclusion: Therefore, it is expected that community health nurses and related parties can follow up by providing regular health education and training to VHV or by developing more innovative educational methods that can sustainably increase the capacity of VHV.